THU0349 Early Symptoms of Systemic Lupus Erythematosus (SLE) Recalled by 337 SLE Patients. (15th July 2016) - Leuchten, N.; Milke, B.; Winkler-Rohlfing, B.; Daikh, D.; Dörner, T.; Johnson, S.; Aringer, M.; ,
Abstract : Background: EULAR and ACR have jointly funded a project to develop systemic lupus erythematosus (SLE) classification criteria, aiming at earlier and more accurate classification of the disease. This abstract reports on an early phase of that project, aimed at collecting potential candidate criteria. Since SLE patients usually experience the onset and diagnosis as a critical life event, memories of this time appear remarkably accurate. Objectives: The objective of this study was to identify early symptoms of SLE from the patient perspective. Methods: As approved by the local ethics committee, we conducted a cross-sectional survey of German SLE patients. An anonymous self-report questionnaire was published in the "Schmetterling" the quarterly journal of the "Lupus erythematodes Selbsthilfegemeinschaft", the German SLE patient association. Patients were asked for year of and age at their initial diagnosis. The questionnaire included typical organ manifestations, symptoms and autoantibodies. In addition, patients were asked to add additional symptoms in free text. For each symptom, boxes were provided to indicate the presence of the symptom before diagnosis, in the first year of diagnosis and at the time of completion of the questionnaire. Results: 333 patient questionnaires were completed and mailed. Of the respondents, 93% were female. The respondents' mean age at diagnosis was 36 years, their mean disease duration was 17 years. 83% reported to be definitely ANA-positive. Joint, skin and kidney involvement were reported at 82%, 66% and 33%, respectively. 22% of patients reported fibromyalgia. For the time before and shortly after diagnosis, more than 50% of the patients reported fatigue (89%), joint pain (87%), sensitivity to sunlight (79%), myalgias (76%), rash (71%), fever (54%), Raynaud's (52%) and hair loss (51%). Approximately one third (37%) affirmed shortness of breath. Free text symptoms reported frequently before or early in diagnosis are listed in Table 1 . Conclusions: For a Caucasian European SLE patient population, the overall characteristics suggested meaningful representation. While many symptoms were reported as expected, a significant number of patients volunteered gastrointestinal complaints and symptoms of the central and peripheral nervous system. Solicitation of self reported information from the patient perspective has not been widely used in the development of classification criteria for SLE. These data add to the information on early SLE symptoms that may help improve classification of early SLE. Disclosure of Interest: None declared